A simple wave/power flow analysis method for vibration control of large cable-frame structures. (September 2022) - Tang, Yaqiong; Wang, Xiaokai; Zhou, Xin; Liu, Tianming
A cable-frame structure typically has low damping and a low fundamental frequency and is modally rich. It is likely to generate sustained vibration when disturbed. Unwanted vibration of such a structure must be caught and controlled to ensure its structural safety and design performance. To overcome the disadvantages of high frequency distortion and modal truncation arising from modal control methods, wave control methods have been suggested. However, they generally involve establishing and solving numerous wave equations, an expensive procedure that may make the vibration control for large and/or complex structures inefficient or even impractical. This study presents a simple analytical approach for the vibration control of large cable-frame structures. The approach is divided into two stages. First, the exact frequency-domain solution is obtained by a dynamic stiffness method in which the infinite degrees of freedom of each flexible component are reduced into only several degrees of freedom at its two endpoints. Second, formulas for calculating the local wave and power flow are deduced based on the global exact solution so that the local wave control information can be extracted from the global response solution. Using this approach, the dynamic response and wave and power flow analysis are carried out for two typical cable-frame structures, leading us to suggest several control measures for suppressing vibration. The approach, if proven to be effective, can be readily applied to vibration control of large cable-frame structures.